Fundamentals of world regional geography - Hobbs, Joseph J.; Dolan, Anrew (Australia Brooks/Cole,Cengage Learning, 2013)
Presents interactive learning, study, and exam preparation tools along with comprehensive text content for one semester/quarter courses. This title helps you understand the eight world regions, including the historical, cultural, economic, political, and physical aspects that create regional unity, give them personality, and make them newsworthy.
1. Objectives and tools of world regional geography -- 2. Physical processes and world regions -- 3. Human processes and world regions -- 4. Europe -- 5. Russia and the near abroad -- 6. The Middle East and North Africa -- 7. South and East Asia -- 8. Oceania -- 9. Sub-Saharan Africa -- 10. Latin America -- 11. The United States and Canada.
Keywords: Geography